2019
DOI: 10.1108/rausp-01-2019-0014
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial orientation and firm performance: an updated meta-analysis

Abstract: Purpose The purpose of this paper is to analyze the relationship between entrepreneurial orientation (EO) and organizational performance through an updated and extended meta-analytic review that includes EO, mediators, moderators and performance results. Design/methodology/approach Using Pearson correlations as effect size statistics, and based on 80 independent samples from 78 studies, with a total sample size of 19,514 cases, the meta-analysis consolidates the empirical findings of this field of research. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 45 publications
(128 reference statements)
0
30
0
2
Order By: Relevance
“…Banyak faktor yang dapat mempengaruhi kinerja suatu perusahaan, salah satu nya yaitu Orientasi Kewirausahaan. Beberapa penelitian terdahulu menunjukan hasil bahwa orientasi kewirausahaan dapat meningkatkan kinerja perusahaan (Anlesinya et al, 2015;Hutahayan, 2019;Kim & Kim, 2016;Magaji et al, 2017;Soares & Perin, 2019). Faktor internal dan eksternal perusahaan dapat memoderasi hubungan antara orientasi kewirausahaan dan kinerja (Lumpkin & Dess, 1996).…”
unclassified
“…Banyak faktor yang dapat mempengaruhi kinerja suatu perusahaan, salah satu nya yaitu Orientasi Kewirausahaan. Beberapa penelitian terdahulu menunjukan hasil bahwa orientasi kewirausahaan dapat meningkatkan kinerja perusahaan (Anlesinya et al, 2015;Hutahayan, 2019;Kim & Kim, 2016;Magaji et al, 2017;Soares & Perin, 2019). Faktor internal dan eksternal perusahaan dapat memoderasi hubungan antara orientasi kewirausahaan dan kinerja (Lumpkin & Dess, 1996).…”
unclassified
“…As one of the most important concepts in the entrepreneurship literature (Rauch, Wiklund, Lumpkin, & Frese, 2009; Soares & Perin, 2020), EO has been conceived in two ways: as a unidimensional and a multidimensional construct (for a more systematic discussion, see Covin & Lumpkin, 2011). As originally conceived by Miller (1983) and developed by Covin and Slevin (1988, 1989), the unidimensional conceptualization posits that an entrepreneurial firm manifests innovativeness, proactivity, and risk‐taking concurrently (Covin & Lumpkin, 2011).…”
Section: Eo Rhetoric Over Time and Health Science Firm Valuationmentioning
confidence: 99%
“…The multidimensionality of EAO allows researchers to study the effect of EAO on business performance (Pulka, 2018). Some indicated that EAO positively affects business performance, whilst others indicated otherwise (Soares & Perin, 2020). The entrepreneurial Attitude Orientation (EAO) model was first introduced by Robinson et al (1991).…”
Section: Entrepreneurial Attitude Orientation (Eao)mentioning
confidence: 99%